THU0366 SYSTEMATIC CORONARY RISK EVALUATION (SCORE) MISCLASSIFIES CARDIOVASCULAR RISK IN ANTISYNTHETASE SYNDROME: RESULTS OF THE PILOT MULTICENTRIC STUDY RI.CAR.D.A. (13th June 2020) - Triantafyllias, K.; Klonowski, A.; Cavagna, L.; Drott, U.; Voll, R.; Fiehn, C.; De Blasi, M.; Wendel, S.; Bergner, R.; Schwarting, A.
Abstract : Background: Antisynthetase Syndrom (ASyS) is an autoimmune overlap disease characterized by antiaminoacyl-tRNA-synthetase (anti-ARS) antibodies and the classic triad of arthritis, myositis and interstitial lung disease (ILD) (1). Markers of cardiovascular (CV) or cerebrovascular (CVB) risk have never been examined in ASyS. Objectives: Aim of this study (RIsk of CARdiovascular Disease in ASyS: RI.CAR.D.A.) was to test the ability of an established traditional CV risk prediction score (Systematic Coronary Risk Evaluation-SCORE) and its EULAR modified version (mSCORE) to identify ASyS patients at high CV risk. Moreover, we sought to examine for the first time associations of CV surrogate markers with clinical and immunological ASyS parameters. Methods: SCORE/mSCORE and the gold standard marker of aortic stiffness (carotid-femoral pulse wave velocity-cfPWV) were examined in patients with ASyS and healthy controls in a multicenter setting (6 Rheumatology Centers). Moreover, sonography of the common- (CCA), internal- (ICA) and external- (ECA) carotid arteries was performed in subsets of both groups, evaluating carotid intima-media-thickness (cIMT), plaques and duplex-sonographic indices of CBV risk such as the resistance- (RI) and pulsatility-index (PI). Results: We recruited 66 ASyS patients with different anti-ARS and 88 controls. According to mSCORE 5/50 (10% ) of the patients had high CV risk. However, cfPWV and carotid sonography (CS) revealed an increased CV risk in 21.2% and subclinical carotid arteriosclerosis (plaques and/or cIMT>0.9 mm) (SCA) in 85.7% of the patients respectively. ROC analyses showed similarly poor diagnostic performances of SCORE/mSCORE in comparison to cfPWV (>10 m/s ) and SAC by areas under the curve (AUC) of 0.56 (95%CI=0.39-0.73 ) and 0.63 (95%CI=0.3-0.96), respectively. cfPWV and SCA were higher in ASyS patients compared to controls ( padj=0.021 and p=0.003, respectively). cfPWV and cIMT correlated in the patient group significantly with age ( r=0.679; p<0.001 and r=0.664; p<0.001, respectively ). Moreover, cfPWV correlated with BMI ( padj=0.001 ) and diabetes (padj=0.043 ). ACC-RI and ACC-PI showed significant associations with a marker of myositis activity [creatine phosphokinase (CPK): r=0.629 ; p=0.012 and r=0.574 ; p=0.032, respectively]. Finally, ACI-RI and ACI-PI values were higher in patients with ILD (both; p=0.039 ). Conclusion: This is the first report of higher aortic stiffness and SCA in ASyS patients compared to controls. Active myositis and presence of ILD were associated with higher CVB risk parameters. Furthermore, SCORE/mSCORE performed poorly in identifying patients at high CV risk and carotid arteriosclerosis compared to cfPWV and CS respectively. Thus, cfPWV and CS could improve CV and CBV screening in ASyS patients. References: [1]Cavagna L, et al. Clinical Spectrum Time Course in Anti Jo-1 Positive Antisynthetase Syndrome. Medicine 2015;94:1144. Disclosure of Interests: None declared